Threshold concepts: linking complex meaning in financial instruments with students’ prior knowledge in accounting and their lived experiences - Lubbe, I.; Bardien, M. (South African Journal of Higher Education, 2025)
Educators often face challenges in teaching accounting concepts and terminology in a way that helps students truly understand their meaning. In the specialised field of financial instruments, identifying and foregrounding the complex meanings of threshold concepts is often challenging. This study identifies five threshold concepts in accounting for financial instruments and describes how these concepts are bounded in the financial accounting discipline. Student participants describe how they navigate through the liminal space of troublesome knowledge to transformative knowledge and whether these concepts, once grasped, enable the irreversibility of knowledge and understanding. The findings indicate that students experienced the concepts conceptually difficult and troublesome, specifically relating to language. The findings suggest that connecting threshold concepts with prior knowledge and contextualising their meaning with students’ lived experiences led to irreversible knowledge.